Miscibility of Narrative Heterogeneity: Ian McEwan’s Sweet Tooth as a Hybrid Postmodernist Metafiction - Seyed-Javad Habibi; Sara Soleimani-Karbalaei (Critical Literary Studies)
Delving into the narration of Ian McEwan's Sweet Tooth (2012), this enquiry unravels the threads of conventional realistic narrative and avant-garde postmodernist one in the tapestry of the novel, arguing that through the miscibility of these two heterogeneous modes of narration McEwan constructs a narrative meta-design that innovatively adds an enigmatic dimension to the spy novel genre. In his dual narrative that depends on verisimilitude as well as self-conscious reflexivity, he once again, a decade after his Atonement (2002), demonstrates his literary taste for bridging the "past" and "present." Marinating his narrative in Cold War events, and adding a dash of what Linda Hutcheon calls "historiographic metafiction," he makes a postmodern signature dish that sustains its paradoxical hybridity: a representational self-reflexivity or an anti-representational reflexivity. Aligned with Monica Cojocaru's detection of a "metafictional twist" in the novel as a part of her comparative investigation, this study discusses that Sweet Tooth's dual narrative makes it eligible to wear the postmodern badge.